2017
DOI: 10.1016/j.jpowsour.2017.01.077
|View full text |Cite
|
Sign up to set email alerts
|

In operando neutron diffraction study of LaNdMgNi9H13 as a metal hydride battery anode

Abstract: La 2 MgNi 9 -related alloys are superior metal hydride battery anodes as compared to the commercial AB 5 alloys. Nd-substituted La 2-y Nd y MgNi 9 intermetallics are of particular interest because of increased diffusion rate of hydrogen and thus improved performance at high discharge currents. The present work presents in operando characterization of the LaNdMgNi 9 intermetallic as anode for the nickel metal hydride (Ni-MH) battery. We have studied the structural evolution of LaNdMgNi 9 during its charge and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 45 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…This results in an increased hydrogen diffusion coefficient and improved high rate dischargeability of the annealed alloy. An improvement in the electrochemical characteristics after the annealing was observed by us earlier when studying AB3 and A2B7 type alloys, and the values of specific capacitance, HRD, and cyclic stability obtained in this study are quite comparable with the data for the La-Mg-Ni alloys [39][40][41][42][43][44]. Further studies of the effect of the rare earth metals on the improved electrochemical performance of the Zr-based Laves type alloys are required to better understand the mechanism governing catalytic interaction between the main phase and the rare earth containing secondary phases, to systematically extend observations available for the multiphase Zrbased alloys doped by La, Ce, Pr or Nd [45] or Zr-based C15 type Laves phase alloys doped by 3 wt.% La [46].…”
Section: Electrochemical Propertiessupporting
confidence: 90%
“…This results in an increased hydrogen diffusion coefficient and improved high rate dischargeability of the annealed alloy. An improvement in the electrochemical characteristics after the annealing was observed by us earlier when studying AB3 and A2B7 type alloys, and the values of specific capacitance, HRD, and cyclic stability obtained in this study are quite comparable with the data for the La-Mg-Ni alloys [39][40][41][42][43][44]. Further studies of the effect of the rare earth metals on the improved electrochemical performance of the Zr-based Laves type alloys are required to better understand the mechanism governing catalytic interaction between the main phase and the rare earth containing secondary phases, to systematically extend observations available for the multiphase Zrbased alloys doped by La, Ce, Pr or Nd [45] or Zr-based C15 type Laves phase alloys doped by 3 wt.% La [46].…”
Section: Electrochemical Propertiessupporting
confidence: 90%
“…In this sense, in situ/in operando characterization techniques cover a major field of capabilities under development at worldwide large facilities and, to an extensive scale, on laboratory level . Many examples of these techniques were applied to the study of materials related to batteries, SOFCs, and catalysis. However, the kind of simultaneous measurements conducted in this work has not yet been reported for protonic conductor materials, despite the fact that the simultaneous characterization of crystallographic and electrochemical properties is fundamental for understanding H-transport processes as well as PC-SOFC limitations and advantages.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, D7 site (RNi 3 tetrahedra inside the AB 2 -type layers) is not occupied in the La 1.5 Y 0.5 MgNi 9 D 12.4 , while in contrast it is filled by 12% in La 2 MgNi 9 D 13 . Similarly, a depopulation of the D7 site has been also observed in LaNdMgNi 9 D 12.9 22 and was related to the smaller unit cell volume as compared to that of the La 2 MgNi 9 D 13 . 15…”
Section: Resultsmentioning
confidence: 59%
“…In contrast, Y occupies both the 3a and 6c sites in the mentioned layers, similar to the findings of our earlier publication for the LaNdMgNi 9 alloy (were Nd acted as an analogue of Y). 22 A different conclusion has been earlier reached in the reference publication. 23 It has been reported that in the isostructural PuNi 3 -type LaY 2 Ni 9 compound Y atoms preferentially occupy the 6c site (AB 2 layer) while La atoms are mostly located in the 3a site (AB 5 layer) leading to a partial ordering in the ternary compound formed in the La 1−x Ce x Y 2 Ni 9 (x Ce = 0, 0.5 and 1) alloys.…”
Section: Dalton Transactionsmentioning
confidence: 79%
See 1 more Smart Citation